The Effect of Canva Teaching Media to The Writing Ability of Eighth Grade Students of SMP Teladan Pematangsiantar Pematangsiantar on a Descriptive Text - Purba, Desmantha; Siahaan, Sanggam; Sinurat, Bloner (The Future of Education Journal, 2024)
Researcher decided to implement Canva Application in this research. The aim of this research is to determine the effect of using Canva as teaching media on students' ability in writing descriptive text in the eighth grade of SMP Swata Teladan Pematangsiantar in 2024/2025 academic year. This research used a quasi-experimental design with quantitative methods. For the sample, in the experimental class and control class the number of students was the same, namely 30 people. The experimental class VIII-B and the control class VIII-2 and to analyze the data, researchers used a t-test formula to find out whether using Canva influenced students' writing ability in descriptive text. In the experimental class the average pre-test score was 60.9 and post-test was 77.2 and, in the control class the average pre-test score was 60.8 and post-test was 71.2. For the standard deviation in the class experimental is 369 and the standard deviation in the control class is 296. The result is that the t-test must be the highest of the t-table with a significance level of 5% (6,781 > 1,672). Based on the findings of this research, the researcher concluded that the alternative hypothesis (Ha) was accepted, and the null hypothesis (H0) was rejected. Thus, it can be concluded that using Canva affects students' descriptive text writing skills, particularly in the eighth grade.